Never too late? An advantage on tests of auditory attention extends to late bilinguals - Bak, Thomas H.; Vega-Mendoza, Mariana; Sorace, Antonella (Frontiers in Psychology, 2014)
Recent studies, using predominantly visual tasks, indicate that early bilinguals outperform monolinguals on attention tests. It remains less clear whether such advantages extend to those bilinguals who have acquired their second language later in life. We examined this question in 38 monolingual and 60 bilingual university students. The bilingual group was further subdivided into early childhood, late childhood and early adulthood bilinguals. The assessment consisted of five subtests from the clinically validated Test of Everyday Attention (TEA). Overall, bilinguals outperformed monolinguals on auditory attention tests, but not on visual search tasks. The latter observation suggests that the differences between bilinguals and monolinguals are specific and not due to a generally higher cognitive performance in bilinguals. Within the bilingual group, early childhood bilinguals showed a larger advantage on attention switching, late childhood/early adulthood bilinguals on selective attention. We conclude that the bilingual advantage extends into the auditory domain and is not confined to childhood bilinguals, although its scope might be slightly different in early and late bilinguals.